2011
DOI: 10.1111/j.1365-2648.2011.05765.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a relaxation training programme on immediate and prolonged stress responses in women with preterm labour

Abstract: The relaxation-training programme could improve the stress responses of women with preterm labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 32 publications
4
17
3
2
Order By: Relevance
“…While previous studies [31, 32] reported a reduction in state anxiety scores following a GI intervention, the findings of this study are consistent with those studies [34, 35] which found no reduction in state anxiety scores. While state anxiety is a common emotional reaction to stress and has been associated with negative health outcomes, recent research suggests that pregnancy anxiety, a newer concept, is one of the most potent maternal risk factors for adverse outcomes [4].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…While previous studies [31, 32] reported a reduction in state anxiety scores following a GI intervention, the findings of this study are consistent with those studies [34, 35] which found no reduction in state anxiety scores. While state anxiety is a common emotional reaction to stress and has been associated with negative health outcomes, recent research suggests that pregnancy anxiety, a newer concept, is one of the most potent maternal risk factors for adverse outcomes [4].…”
Section: Discussionsupporting
confidence: 92%
“…There was a statistically significant reduction in perceived stress scores at 8 weeks (time 2) but not at 12 weeks (time 3) in the GI compared to UC group. The significant decrease in PSS scores for the GI group at 8 weeks has not been reported in previous studies with pregnant women [31, 32]. A possible explanation for this finding may be related to the selection of images for this study.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…The VAS has generally been used to assess levels of subjective stress, satisfaction, and childbirth experience and labor pain in perinatal fields in Japan and China [27][28][29][30]. In this study, the VAS consisted of a 100-mm horizontal ungraded line with two endpoints with "no stress" labeled on the left and "severe stress" on the right.…”
Section: Visual Analog Scale (Vas)mentioning
confidence: 99%